(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article is dedicated to consideration of John Cheever’s objective world in his novel «Falconer». The purpose of the article is an in-depth study of American symbolist, as well as the study of his work «Falconer» from different angles. Cheever works show a remarkable observation and the power of creative imagination. The main theme of his books – the loneliness of a man whose motives are often in conflict with public regulations. Like John Updike, who glorifies in the past leaving community of people professing Protestant values, Cheever puts into the base of his artistic motives the world of flight and return to normal. The novel called «Falconer» became a bestseller in 1977, this success inspired him, and he, like his hero, is reborn to life. The hero of the novel Ezekiel Farragat is sentenced to imprisonment for the murder of his brother. Getting in the colony, he is forced to look within those moral qualities that would survive in this rough, cruel world. Cheever writes about suffering and redemption, faith in the miraculous resurrection of the soul, a new birth of man, condemned to death.